Cross-Borsder Mergers and Acquistions - Whitaker, Scott C. (John Wiley & Son, 2016)
In this book, readers will gain unique perspectives and guidance to hepl them to understand the complexities and risks of doing M&A across national, cultural, and linguistics boundaries, including: - Legal, financial, social, and political interdependencies with cross-border intergration. - Region-and country - specific trend and deal planning tips. - The role of culture in cross - border M&A. - M&A considerations for China and Japan.